Groundnut Ringspot Virus in Florida - Eugene McAvoy; Scott Adkins; Craig Webster; Charles Mellinger; Loren Horsman; Galen Frantz; Stuart Reitz; Shouan Zhang (EDIS)
Groundnut ringspot virus was recently identified in tomatoes in South Florida — the first report in the United States. It can infect tomato plants at all stages of growth and lead to unmarketable fruits or plant death. This 4-page fact sheet shares what is known about the symptoms, host range, disease transmission, and management. Written by Eugene McAvoy, Scott Adkins, Craig Webster, Charles Mellinger, Loren Horsman, Galen Frantz, Stuart Reitz, and Shouan Zhang, and published by the UF Department of Plant Pathology, July 2011.